Evaluasi Pengaruh Rasio Likuiditas dan Solvabilitas terhadap Kinerja Keuangan Pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2023 - Puput Widiyasari; Dwiyatmoko Puji Widodo; Yuni Siti Nuraeni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Indonesia's telecommunications sector has grown rapidly since 1961. Telephone and internet access have now expanded, including in remote areas, driving digital economic growth. However, infrastructure challenges in rural areas, service quality, costs, and regulatory issues still hinder the industry's development. This study aims to evaluate the financial performance of telecommunications sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period, focusing on the analysis of liquidity and solvency ratios and their impact on financial stability.